Characteristics of Domestic Wastewater from Shopping Centres, Office Buildings, and Hospitals in Jakarta, Indonesia - Herman, Anggit; Firdaus, Najmi; Pancawati, Juwarin; Abidin, Thoriq (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Understanding the characteristics of domestic wastewater is crucial for designing effective wastewater treatment facilities that comply with regulatory standards. This study examined key parameters, including pH, BOD, COD, TSS, oil and grease, ammonia nitrogen, and total coliform, outlined by Indonesia’s Ministry of Environment and Forestry (MoEF) under their regulation. Samples were collected monthly over a 12-month period from three types of facilities: shopping centers, office buildings, and hospitals. The results indicated significant variability among the sites. The shopping center recorded the highest concentrations of BOD and TSS, with values of 231 mg/L and 366 mg/L, respectively, while the hospital showed elevated COD levels, reaching 725 mg/L. Its processing requires a wastewater treatment plant that aims to reduce various parameters that exceed the threshold based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.68 /Menlhk/Setjen/Kum I/8/2016 on Domestic Waste Quality Standards. These findings underscore the need for tailored wastewater treatment approaches based on facility type to mitigate environmental impacts and maintain water quality standards.